2012
DOI: 10.1016/j.jjcc.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of social support and coping strategies with acute coronary syndrome: A case–control study

Abstract: Improvement in social support and adaptive coping strategies should be considered in patients with chronic ischemic heart disease (IHD) to reduce the risk of ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
2
15
0
2
Order By: Relevance
“…These findings should be interpreted cautiously due to the small sample size, but they are consistent with previous work showing that coping strategies and disease-related beliefs play an important role in health behaviours and disease adjustment [23,24]. By showing that patients' coping strategies after a cardiac event are more strictly associated with future disease severity than expressed symptomatology, they support the 9 emphasis of the constructive perspective on the different modalities that individuals use to make sense of the events that happen to them and to deal with these events [5].. Also, the finding that emotion-focused coping was a better predictor of cardiac functioning than the other forms of coping is in line with the constructivist view that emotions play a crucial role in the way we attribute meaning to life experience [5].…”
Section: Discussionsupporting
confidence: 91%
“…These findings should be interpreted cautiously due to the small sample size, but they are consistent with previous work showing that coping strategies and disease-related beliefs play an important role in health behaviours and disease adjustment [23,24]. By showing that patients' coping strategies after a cardiac event are more strictly associated with future disease severity than expressed symptomatology, they support the 9 emphasis of the constructive perspective on the different modalities that individuals use to make sense of the events that happen to them and to deal with these events [5].. Also, the finding that emotion-focused coping was a better predictor of cardiac functioning than the other forms of coping is in line with the constructivist view that emotions play a crucial role in the way we attribute meaning to life experience [5].…”
Section: Discussionsupporting
confidence: 91%
“…), and lack of social support leads to decreased survival and poorer prognosis among people with CHD (Albus , Roohafza et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Informational and emotional supports were primarily perceived at a high level, while the weakest dimension of social support perceived was functional support. This outcome is distinct because, according to previous studies, there is considerable evidence that a low level of perceived social support is an independent risk factor for CHD (Barth et al 2010), and lack of social support leads to decreased survival and poorer prognosis among people with CHD (Albus 2010, Roohafza et al 2012). There were a few noteworthy findings regarding dimensions of social support and background variables.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Social support: Roohafza et al, found a significant negative association between social support and acute coronary syndrome [27]. Cheraghi et al found a significant relationship between perceived social support and quality of life [28].…”
Section: Introductionmentioning
confidence: 99%